Nanoscale Friction and Wear of Phosphate Laser Glass and BK7 Glass Against Single CeO2 Particle by AFM. Issue 4 (16th January 2015) - Yu, Jiaxin; Yuan, Weifeng; Hu, Hailong; Zang, Hongbin; Cai, Yong; Ji, Fang; Pharr, G.
<x xml:space="preserve">Abstract</x> CeO2 (ceria) particles are considered as a type of ideal polishing particle used to polish glass substrate. The friction and wear of glass substrates caused by a single CeO2 particle is the origin of material removal in polishing, but this has not been well‐understood in previous research. In this investigation, the nanoscale friction and wear behaviors of the Nd‐doped phosphate laser glass and the BK7 optical glass were quantitatively studied against a single CeO2 particle by an atomic force microscopy in humid air. The investigations on the phosphate laser glass indicate directly that this type of glass cannot resist the wear when it rubs against the single CeO2 particle in the elastic contact in humid air. During the test, high friction coefficient and severe material removal were observed in the friction process. The chemical activity of the CeO2 particle was proved to be a cause that induces the tribochemical wear of the phosphate laser glass since the tribochemical wear cannot occur when a chemically inert diamond tip was used. On the other hand, the BK7 glass presented a much better wear‐resistance, where the friction coefficient is relatively lower and the expected tribochemical wear cannot occur in the same stress condition as compared with that for the phosphate laser glass, and the damage of the BK7 glass is more like the mechanical peeling of the asperities on the glass surface. The results provide new insights into single‐asperity friction and wear of glass materials, which would be useful in understanding the mechanisms of friction and material removal in polishing glass materials with ceria slurry.